1984
DOI: 10.1044/jshr.2702.257
|View full text |Cite
|
Sign up to set email alerts
|

Tympanometric Changes at 226 Hz and 678 Hz Across 10 Trials and for Two Directions of Ear Canal Pressure Change

Abstract: The influence that repeated tympanometric trials have on the aural-acoustic admittance characteristics of the middle-ear transmission system was studied in 24 young adults. The 226-Hz and 678-Hz data were generated by concurrently digitizing the conductance and admittance tympanograms at 25 daPa/s for both ascending and descending pressure directions. Ten successive trials for each frequency and direction of pressure change were made. Changes in admittance corrected for ear canal volume across the 10 tympanome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…To minimize the tympanometric preconditioning effect in research on tympanometry, previous investigators suggested collecting desired data after three to five tympanometry runs (Gaihede, 1996;Wilson et al, 1984). Our study has demonstrated that the second and third trials of WBTymp account for more than half of the total EA change by eight trials.…”
Section: Implications For Applications Of Wai Measurementsmentioning
confidence: 67%
See 4 more Smart Citations
“…To minimize the tympanometric preconditioning effect in research on tympanometry, previous investigators suggested collecting desired data after three to five tympanometry runs (Gaihede, 1996;Wilson et al, 1984). Our study has demonstrated that the second and third trials of WBTymp account for more than half of the total EA change by eight trials.…”
Section: Implications For Applications Of Wai Measurementsmentioning
confidence: 67%
“…Previous studies on nine to 10 successive runs of 226-and 678-Hz tympanometry have revealed a systematical increase in acoustic admittance of the middle ear by approximately 12% to 14% (Gaihede, 1996;Osguthorpe & Lam, 1981) or a slightly higher percentage (Wilson et al, 1984). These studies also observed that about half of the total change occurred at the second trial.…”
Section: Consecutive Tympanometry Runs and Middle Ear Acousticsmentioning
confidence: 87%
See 3 more Smart Citations